Competitive Strategy Suggestions for Electric Vehicle Companies -- Based on Consumer Purchasing Driving Factors - Zhou, Yiying (2022)
Promoting the use of electric vehicles can better contribute to environmental protection. Over the past decade, governments have provided a lot of support to the electric vehicle industry, attracting many companies enter into the industry. The sharp increase in sales and the market’s optimistic attitude towards the electric vehicle industry has prompted fierce competition in the industry. Previous studies on the strategies of electric vehicle companies focused on the analysis of corporate value chain and external environment, and paid little attention to the needs of consumers. This paper combines the consumer purchase theory with the corporate competitive strategy and helps the electric vehicle company to develop competitive strategy by determining the driving factors that affect consumers’ purchase of electric vehicles. To get a more complete understanding of consumer buying factors, this paper adopts mixed methods approach including semi-structured interview and survey. The research finds that consumers still believe that government policies have a significant impact on the development of the electric vehicle industry, mainly because of the attractiveness of environmentally friendly initiatives and car purchase subsidies to consumers. Through the investigation, this paper suggests that electric vehicle companies obtain major competitive advantages mainly by means of image differentiation, service differentiation and cost reduction. If the enterprise is rich in resources, it can adopt a focus strategy to focus on the battery technology of electric vehicles or to meet a specific market segment, otherwise the focus strategy will be risky.